Obstacles to the enforcement of sovereignty in the land border area of the Unitary State of Republic Indonesia (NKRI) with the Republic Democratic Timor Leste (RDTL) - Bire, Chatryen M. Dju; Radja, Melinda Ratu; Silvester, Agustinus; Tungga, Axel Rudolf Alexander (Goodwood Publishing, 2024)
Purpose: This study examines the enforcement of Indonesia’s territorial sovereignty in North Insana District, North Central Timor Regency, and Oecusse District, Democratic Republic of Timor Leste (RDTL). After Timor Leste’s secession in 1999 through a UN-supervised referendum, the new state faced the challenge of delineating borders with neighboring countries, especially Indonesia, to consolidate sovereignty and avoid disputes. Method: A dual-method approach was employed: library research—covering books, treaties, seminar proceedings, correspondence, and online resources—and empirical fieldwork in the border region. Results: The findings reveal two key issues in the RI–RDTL border area, particularly in North Insana. First, unresolved boundaries foster illegal cross-border activities by communities who feel excluded from development and rely on neighboring states for daily needs. Second, development gaps in the border region, illustrated by micro-level traffic in Haumusu Wini Village, underscore the need for a more inclusive strategy. Sovereignty challenges stem from limited resources, poor infrastructure, restricted accessibility, and insufficient funding. Conclusions: The study concludes that Indonesia’s sovereignty along the RDTL border remains constrained by resource scarcity and unresolved territorial demarcation, necessitating stronger bilateral cooperation. Limitations: The main limitations are time constraints and the distance of the research site, which restrict broader observation. Contributions: The research emphasizes the importance of effective border management to safeguard territorial sovereignty and strengthen comprehensive state protection.